The Effect of Inhibition of Dopamine D2 Receptors on Some of the Peripheral Blood Mononuclear Cells of the Rat under Food restriction - khatereh Noormohammadi; Farrin Babaei Balderlou; Seyyed Meysam Abtahi Foroushani (Fasa University of Medical Sciences, 2018)
Background & Objective: In previous studies, the effects of food restriction on the changes in immune responses and brain dopamine content have been determined. On the other hand, it has been shown that immune cells, in addition to dopamine production, also have dopamine receptors. The purpose of this study was to evaluate the effect of inhibition of D2 dopamine receptors on several functions of monocytes of peripheral blood in rat under food restriction Materials & methods: In this experimental study, 36 male Wistar rats (weighing 200-250 gr) were allocated into six groups (n=6), including control groups, food restriction (25%), food restriction (50%), food restriction (75%), food restriction 75% and Sulpiride and rats treated with Sulpiride. Sulpiride was injected Intracerebroventricular at a concentration of 50 μg / rat on day 21 after the study initiation. At the end, the Rats were bled and peripheral blood mononuclear cells were isolated by ficoll gradient method. Results: Food restriction caused a significant decrease in the activity of monocyte cells of gradient of peripheral blood mononuclear cells like neutral red uptake test and respiratory burst (NBT reduction test) simultaneously with decreasing lymphocytes proliferation after stimulation with phytohemagglutinin. Administration of Sulpiride with a 75% Food restriction resulted in the improvement of these functions of monocyte cells of gradient of peripheral blood mononuclear cells as well as lymphocyte proliferation. Conclusion: Intracerebroventricular administration of dopamine D2 receptor antagonists (sulpiride) effectively inhibited the effects of a severe dietary restriction on the suppression of immunity system.